Professional Tennis (ATP Tour) and number of medical treatments in relation to type of surface - Bastholt, P. (2000)
The purpose of this paper is to discuss the correlation between playing surfaces and the incidence of injuries in men`s professional tennis players.. It is generally assumed that hard courts cause more injuries to the lower extremities, hip and lower back than either clay or grass, due to a lack of cushioning and higher. Four major playing surfaces can be found in men`s pro tennis: clay court, hard court, grass, and carpet. By analyzing the treatment data collected on these surfaces , one can attempt to gauge the relative risks of playing on different playing surfaces over time. In this study, the treatment data was collected by ATP Tour Sports Medical Trainers over a three year period. Subjects and methods: Five ATP Tour Sports Medical Trainers supervise the medical coverage of all ATP Tournaments, ensuring high quality care according to preset standards. They are supported by local massage therapists and/or physiotherapists, which perform massage treatments. Every treatment executed by the ATP Tour Sports Medical Trainer was registered and kept on a weekly updated data base, according to a standardized treatment protocol developed by the ATP Tour Medical Services Committee. A treatment is defined as a medical contact between a player and the medical staff of the ATP Tour. Massage treatments by massage and physiotherapists are not included. The tournaments studied are 9 tournaments on indoor and outdoor hard courts as well as indoor carpet leading up to the clay court season; 9 clay court tournaments, and 5 grass court tournaments immediately following the clay court tournaments. The data analyzed were collected from 1995-1997. Subjects are the men`s professional singles and doubles tennis players, competing in the aforementioned tournaments. Results: It was found that the distribution of treatment localization was essentially the same on all three surfaces. Lower extremities cover 35-50 %, low back and spine around 20 %, arm and shoulder 20%, and somewhere in between 15-30 % represent `other` treatments including massage and stretching. In this study only lower extremity treatments are discussed. Grass 456 treatments were given during 5 tournaments, during which a total of 1092 matches were played. This gives a frequency of 0.42 treatments per match played. Hard Court/Carpet 656 treatments were given during 9 tournaments, in which a total of 1770 matches were played. This gives a frequency of 0.37 treatments per match. Clay 475 treatments were given during 9 tournaments in which a total of 2361 matches were played. This gives a frequency of 0.20 treatments per match played. In order to determine the relative risk of treatment on the diffferent court surfaces, statistical analysis was performed using the Poisson-regression, leading to the following results. The risk of having to receive treatment is lowest on clay and highest on grass. The relative risk of hard court compared to grass is 0.80 (P=0.01), which means the risk is less on hard court. However, the risk is higher on hard court when compared to clay: 2.3 (P=0.001). The risk is lowest on clay compared to grass 0.35 (P=0.0001). In other words: approximately half as many treatments were given during tournaments played on clay, compared to tournaments played on hard-court and on grass.This is shown in table 1. Discussion: The general conclusion is that playing on either grass or hard court is resulting in an increased number of treatments than playing on clay. There are well known differences in how tennis is played on grass and on clay. On grass, the game is generally more aggressive with the serve and return of serve critical in deciding the outcome of a point. No sliding is possible. Actually, the players claim that the grass-court soles on their shoes are gripping too much. The game on clay includes more lateral movements on the baseline, with the serve much less of a factor. Many exhanges over the net are often necessary to decide a point. On clay the preparation every time the ball is hit is relatively long, and the ball bounces high. On grass the ball often picks up speed when hitting the ground, and the bounce is very low. Tactically and physically these are two different ways of playing tennis. Hard court play is a combination of the grass and clay styles.. Serve and volley can still be used, but more and more frequently we observe baseline rallies. This on a hard, rough surface implies many and long rallies may provoke even more problems with joints and tendons.